Certifications as Catalysts for Enhancing Quality Management Maturity and Sustainability: Evidence from Fish Processing Enterprises in Indonesia - Suseno, Heru; Suadi, Suadi; Jamhari, Jamhari; Rustadi, Rustadi (International Review of Management and Marketing, 2025)
The study aims to explore the correlation among certification, Quality Management Maturity Level (QMML), and Index of Sustainability Performance (ISP) of fish processing firms (FPFs). The QMMLs and the ISPs are compared among four different sizes of FPFs. Data were obtained from 102 certified FPFs in Indonesia. Descriptive statistical methods were used to examine the data to determine the QMML and the ISP and compare them across various firm sizes. The Spearman Rho test indicates a positive correlation between the certification, the QMML, and the ISP. The mean comparison using the Kruskal-Wallis test reveals no difference in the QMML and ISP of FPFs at a significant level of 5% among different-sized organizations. This finding challenges the notion that organizational management and human resource issues make micro and small enterprises (MSEs) fragile and not capable of competing with large-scale firms. MSEs have also been successful in raising the organizational quality management maturity since certification has pushed quality management implementation for enterprises of all sizes. Therefore, it expands understanding about the impact of certification on enhancing the micro-small business. The results can dispel doubts that MSEs cannot compete with large companies. This study can encourage MSEs to achieve sustainable performance.